HUBUNGAN KEPUASAN KERJA DENGAN PRESTASI KERJA PERAWAT DI INSTALASI RAWAT INAP RUMAH SAKIT ISLAM KLATEN - Hartati, Sri; Handayani, Lina; Solikhah, Solikhah (Universitas Ahmad Dahlan, 2011)
Background: Standart evaluation and quality control exlpain that nursery services guarantee a high quality of nursing by involving themselves into quality control in the hospital. Job satisfaction must be created goodly, in order to job morality, disciplined, dedication and job performance can be increased. The employee can work produce or not was depent on motivation, job satisfaction, the level of stress, phisicly condition of job, salary, project of work, aspeck of economy and technics. The aim of this reseach was to know correlation job satisfaction and job performance. Methods: The study was analytic quantitative with cross sectional method. Data were analyzed quantitatively with Product Moment correlation analyze. The population was all of nurse (110 persons) in the nursery room services at the Klaten Islamic Hospital. The tool of the study was questionaire toward 52 respondents. Sample taken by proportional random sampling. Result: The result of the study showed that job satisfaction of nurses was on the moderate level reached (63,5%). Job performance of nurses was on the good level reache (78,8%). There were positive correlation between job satisfaction and job performance, with correlation coefficien r = 0,393 (on the low level); with p=0,004. Conclusion: There were positive correlation between job satisfaction and job performance of nurses. Key words: Job satisfaction, job performance, nurse.